1993
DOI: 10.1002/hlca.19930760814
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Chiroptical Properties of Dimethyl 8,12‐Diphenylbenzo[d]heptalene‐6,7‐dicarboxylate

Abstract: Dedicated to Arnold Brossi on the occasion of his 70th birthday (23. IX. 93) 6,lO-Diphenylbenz[u]azulene (3) was reacted with dimethyl acetylenedicarboxylate (ADM) in the presence of 2 mol-% of [RuH2(PPh3),] in MeCN at 100' to yield a 7:1 mixture of dimethyl 2,6-diphenyl-9,10-benzotricyclo-[6.2.2.0',7]dodeca-2,4,6,9,1 I-pentaene-1 1,12-dicarboxylate (4) and dimethyl 8,12-diphenylbenzo[d]heptalene-6,7dicarboxylate (5; Scheme 2). The tricycle 4, when heated in DMF at 150" for 1 h led to the formation of 81.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…1.1.1. 2-(Hydroxymethyl)- I-methylazulene (2): 0.8-mmol runs gave 2 in yields of 75% (from l a [IS]) and 92% (from l b [7] 3684s, 3602s, 3021m, 2923m, 1601s, 1575s, 1381m, 988m, 788m, 556m, 527m. ' H -N M R : 8.23 (d, J(7,8) = (5) 3.66 (3.79), 321 (4.35), 304(4.31), 292 (sh, 4.19), 251 (3.95),218 (4.09); l,i, 360 (3.77), 308 (4.30), 272 (3.92), 230 (3. (5)); 3.15 (s,); 2.96 (s, Me-C(4)); 1,4,8-trimethylazulene (6b).…”
Section: Experimental Partmentioning
confidence: 99%
See 2 more Smart Citations
“…1.1.1. 2-(Hydroxymethyl)- I-methylazulene (2): 0.8-mmol runs gave 2 in yields of 75% (from l a [IS]) and 92% (from l b [7] 3684s, 3602s, 3021m, 2923m, 1601s, 1575s, 1381m, 988m, 788m, 556m, 527m. ' H -N M R : 8.23 (d, J(7,8) = (5) 3.66 (3.79), 321 (4.35), 304(4.31), 292 (sh, 4.19), 251 (3.95),218 (4.09); l,i, 360 (3.77), 308 (4.30), 272 (3.92), 230 (3. (5)); 3.15 (s,); 2.96 (s, Me-C(4)); 1,4,8-trimethylazulene (6b).…”
Section: Experimental Partmentioning
confidence: 99%
“…Oxidation of 6b: 0.27 mmol of6b were reacted with 1.5 g of MnO, to give *) If not otherwise stated, the oxidation reactions were performed with ca. 10-year-old batch of MnO, ('gefillt, aktiv') (8) [7]. Blue crystals from hexane/Et,O.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…of Ph,C+BF, with respect to the mixture of 23a-d was applied, 28a/28b (70%) were, beside Ph,CH, again the main components in the reaction mixture after treatment with Me,N. [5]. The reaction is also applicable to benz [a]azulene (31) itself and dimethyl acetylenedicarboxylate (ADM) [7] (see also [6]) and opens an easy access to 30 particularly, in view of a new synthesis of 31 that has been developed by us [22] (see also [23] showed that the thermal reaction in aromatic hydrocarbons such as toluene gave the best yields of the benzo[a]heptalenedicarboxylates with a minimum number of by-products (see also [8] [24] [23]), since heptafulvene shows exactly this type of periselectivity in cycloaddition reactions (cf.…”
Section: D23bmentioning
confidence: 99%
“…a) 180-208" in tetralin or decalin or looo in MeCN in the presence of2 mol-% of [RuH2(Ph3P),] (6). b) 180-208" in tetralin or decalin.…”
Section: H (E)/(z)-5 (6%)mentioning
confidence: 99%